Sjögren’s Syndrome 2011
DOI: 10.1007/978-1-60327-957-4_22
|View full text |Cite
|
Sign up to set email alerts
|

The Neurological Manifestations of Sjögren’s Syndrome: Diagnosis and Treatment

Abstract: This chapter addresses the:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 158 publications
(124 reference statements)
0
7
0
Order By: Relevance
“…Sjögren’s syndrome is a chronic inflammatory disease characterized by lymphocytic infiltration and impaired function of the lacrimal and salivary glands. The main manifestations are keratoconjunctivitis sicca and xerostomia, although lymph node and salivary gland enlargement, non-Hodgkin’s lymphoma, myalgia, fatigue and cognitive dysfunction may also occur [ 5 ]. New diagnostic criteria proposed in 2012 by the American College of Rheumatology [ 6 ] include at least two of the following: (1) positive serum anti-SSA and/or anti-SSB antibodies or positive rheumatoid factor and ANA titers 1:320 or higher, (2) a Sjögren’s International Collaborative Clinical Alliance ocular staining score of 3 or higher and (3) lymphocytic sialadenitis with one or more foci of 50 lymphocytes per 4mm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Sjögren’s syndrome is a chronic inflammatory disease characterized by lymphocytic infiltration and impaired function of the lacrimal and salivary glands. The main manifestations are keratoconjunctivitis sicca and xerostomia, although lymph node and salivary gland enlargement, non-Hodgkin’s lymphoma, myalgia, fatigue and cognitive dysfunction may also occur [ 5 ]. New diagnostic criteria proposed in 2012 by the American College of Rheumatology [ 6 ] include at least two of the following: (1) positive serum anti-SSA and/or anti-SSB antibodies or positive rheumatoid factor and ANA titers 1:320 or higher, (2) a Sjögren’s International Collaborative Clinical Alliance ocular staining score of 3 or higher and (3) lymphocytic sialadenitis with one or more foci of 50 lymphocytes per 4mm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The respective frequencies of these individual syndromes are rare: including the sensory neuronopathies (prevalence of ∼1:1000 in SS patients), 29 , 42 , 43 cerebellar degeneration (prevalence of <1:1000 in SS patients), 43 and FTD (prevalence of ∼8:10,000). 44 Therefore, the collective likelihood that these disorders jointly occurred by random chance, and were not mechanistically interrelated, has a probability of ∼1-per-billion.…”
Section: Case Presentationsmentioning
confidence: 99%
“…The primary target organs in pSS are exocrine glands (such as salivary, lacrimal, and sweat glands [1,2]), which are glands of the gastrointestinal and respiratory systems, which confirms the conception of generalized autoimmune epithelitis in this disease. In the absence of therapy, patients can develop systemic manifestations such as various types of lesions in the joints, blood vessels (cryoglobulinemic and hypergammaglobulinemic purpura), lungs, kidneys, and reticuloendothelial (regional and generalized lymphadenopathy, splenomegaly, and hepatomegaly), peripheral, and central nervous system, which can lead to a significant decrease in the quality and life expectancy of the patients [3,4]. According to studies, gastrointestinal involvement (dysphagia) can be observed in up to 80% of patients, and arthralgia is reported to be present in up to 75% of patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…In 15% of patients, the disease debuts in childhood, and in 70% under the age of 50 years. pSS is more common in females, and the ratio to males ranges from 9:1 to 25:1 [3,4]. This phenomenon can be explained by several reasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation